2020
DOI: 10.1124/dmd.120.000122
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Pravastatin Isomerization on OATP1B1-Mediated Transport

Abstract: Pravastatin (PVA) can be isomerized to its inactive metabolite 3'α-iso-pravastatin acid (3αPVA) under acidic pH conditions. Previous studies reported inter-individual differences in circulating concentrations of PVA and 3αPVA. This study investigated the functional consequences of PVA isomerization on OATP1B1-mediated transport. We characterized 3αPVA inhibition of OATP1B1-mediated PVA uptake into HEK293 cells expressing the four different OATP1B1 proteins (*1a, *1b, *5 and *15). 3αPVA inhibited OATP1B1-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Pravastatin and rosuvastatin uptake were facilitated by the organic anion transporting polypeptide transporters and breast cancer resistance protein respectively. 49,52,65 breast cancer resistance protein is highly expressed in the human placenta and facilitates the transport of a wide variety of drugs. 40,66 Since rosuvastatin was efficiently transported by BCRP, the concentration of the rosuvastatin in the STB chamber was decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pravastatin and rosuvastatin uptake were facilitated by the organic anion transporting polypeptide transporters and breast cancer resistance protein respectively. 49,52,65 breast cancer resistance protein is highly expressed in the human placenta and facilitates the transport of a wide variety of drugs. 40,66 Since rosuvastatin was efficiently transported by BCRP, the concentration of the rosuvastatin in the STB chamber was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Pravastatin is primarily metabolized (3′α-iso pravastatin, 6′epipravastatin, 3′α, 5′ β-dihydro-pravastatin, desacyl-dehydro pravastatin, 3′-hydroxy-pravastatin) by glucuronidation and minimally involve CYP enzymes. [49][50][51] Rosuvastatin is predominantly metabolized (N-desmethyl rosuvastatin and rosuvastatin-5S-lactone) by CYP 3A4 and 2D6 enzymes. 52 To note, pravastatin metabolites are inactive and often lead to increased excretion, whereas rosuvastatin metabolites are active and carry out its mechanism of action.…”
Section: Metabolism Of Statins Within the Placenta On-chipmentioning
confidence: 99%
“…Laboratory studies have shown that statins can limit cancer progression by promoting apoptosis and inflammatory responses and by inhibiting cancer cell proliferation, adhesion, and angiogenesis[ 9 - 12 ]. A meta-analysis reported that patients with mCRPC may benefit from treatment with abiraterone or enzalutamide in combination with statins[ 13 ]. In addition to lowering cholesterol, statins compete to inhibit DHEA uptake by binding to solute carrier transporters (SLCO2B1), thereby effectively reducing the pool of androgens available in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this transporter affects the uptake of multiple exogenous drugs, including lovastatin. OATP1B1 inhibition increases lovastatin levels, resulting in increased drug toxicity[ 13 , 14 ]. Statin-induced rhabdomyolysis is dose-dependent, especially when statins are used in conjunction with a muscle-toxic agent or drug that can increase their concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Genetic variation in SLCO1B1 can result in lower amounts of OATP1B1 protein on the basolateral surface of human hepatocytes, or decreased function resulting in diminished hepatocellular uptake. This, in turn, can limit hepatic clearance and cause increased systemic exposure to drug substrates, [4][5][6][7][8][9] which can lead to increased risk for systemic drug toxicity and adverse events. [10][11][12] Additionally, there is also in vitro and in vivo evidence that some genetic variants increase gene expression and function, as well as variants that impact transporter function in a substrate-dependent manner.…”
mentioning
confidence: 99%